Energy Justice in Apartment Buildings and the Spatial Scale of Energy Sustainable Design Regulations in Australia and the UK - Gower, Alexa (Frontiers in Sustainable Cities, 2021)
Energy vulnerability is a growing concern in many OECD countries post-millennium. An increasing number of residents go without heating or cooling necessities to manage the financial strains of increasing energy costs, low wage growth, and rising housing costs. Housing design quality contributes significantly to a dwelling's energy use and the resident's potential energy vulnerability with good orientation enabling passive climate control or, alternatively, poor design resulting in a reliance on artificial heating, cooling, and lighting for livability. Housing design regulations are accepted as an important tool in planning for achieving energy sustainability and mitigating climate change. However, this article argues for greater recognition and knowledge regarding regulation's ability to protect against energy vulnerability at the residential scale, particularly in the growing number of apartments purchased for the rental market in Australia. By observing the energy sustainability of apartments deemed permissible by Australian and UK regulations, this research demonstrates the significance of building scale in regulations when applied to apartments buildings. An energy justice lens reveals a distinction between measurement at the whole building level and the individual apartment/resident scale in this building typology in particular.